2011
DOI: 10.1001/jama.2011.1456
|View full text |Cite|
|
Sign up to set email alerts
|

Association of BRCA1 and BRCA2 Mutations With Survival, Chemotherapy Sensitivity, and Gene Mutator Phenotype in Patients With Ovarian Cancer

Abstract: Context Attempts to determine the clinical significance of BRCA1/2 mutations in ovarian cancer (OvCa) have produced conflicting results. Objective To determine the relationships between BRCA1/2 deficiency (i.e., mutation and promoter hypermethylation) and overall survival (OS), progression-free survival (PFS), chemotherapy response, and whole exome mutation rate in OvCa. Design, Setting, and Patients Observational study of multidimensional genomics and clinical data on 316 high-grade serous OvCa cases that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

39
358
4
9

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 505 publications
(425 citation statements)
references
References 33 publications
39
358
4
9
Order By: Relevance
“…[99][100][101] Previous studies in ovarian cancer suggested that mutations in both genes were associated with similar responses to platinum-based chemotherapy. 101 Recently, Yang et al 102 have reported a series of 316 ovarian cancer patients treated with surgery and adjuvant platinum-based chemotherapy in which BRCA2 mutations were associated with improved outcomes, while BRCA1-mutated or -hypermethylated tumours were not significantly different from BRCA wild-type cases. BRCA2 mutations were also associated with an increased rate of response to primary platinum chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…[99][100][101] Previous studies in ovarian cancer suggested that mutations in both genes were associated with similar responses to platinum-based chemotherapy. 101 Recently, Yang et al 102 have reported a series of 316 ovarian cancer patients treated with surgery and adjuvant platinum-based chemotherapy in which BRCA2 mutations were associated with improved outcomes, while BRCA1-mutated or -hypermethylated tumours were not significantly different from BRCA wild-type cases. BRCA2 mutations were also associated with an increased rate of response to primary platinum chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…234 Several studies have revealed ovarian cancer patients with BRCA1 as well as BRCA2 germline mutations to have a better chance of responding to platinumbased therapy as compared with patients wild type for BRCA1/2 in the primary setting as well as on tumour relapse. 233,[235][236][237][238] Most interestingly, there is experimental (BRCA2) but also results in human tumours (BRCA1 and BRCA2) revealing secondary mutations, restoring BRCA1/2 protein function, to be associated with acquired resistance toward platinum compounds. [239][240][241][242] The fact that mutations affecting both BRCA1 and BRCA2 seem to confer sensitivity to platinum compounds and to PARP inhibitors (see below) clearly implicates the Fanconi complex in drug sensitivity to these compounds.…”
Section: Homologous Recombination Repairmentioning
confidence: 99%
“…30 Since that time, Soslow et al 23 validated the significance of different histologic patterns by describing variant morphologies (SET) in tumors with BRCA germline mutations that are associated with a better prognosis and a better response to chemotherapy. 3,4,[12][13][14][15][16][17][18][19] We previously reported on a separate cohort of high-grade serous carcinomas, showing an association between BRCA-positivity and variant histology (SET-like), younger age, a lower frequency of serous tubal intraepithelial carcinoma, and trends toward improved survival. 24 In this current study, we found that mutations in homologous recombination genes were 6 times more likely to be associated with nonclassic high-grade serous carcinoma histology (70%) than with classic high-grade serous carcinoma histology (28%) (P o0.001), and BRCA1 mutations were 10 times more likely to be associated with nonclassic high-grade serous carcinoma histology (P o 0.001) than classic histology.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 The reliance on alternative end-joining repair pathways subsequently renders homologous recombination-deficient tumors more sensitive to chemotherapy as well as to PARPi. 3,4,[12][13][14][15][16][17][18][19] Only one PARPi has been FDA approved for the treatment of ovarian cancer, olaparib, and this is only in the setting of BRCA mutation and at least three prior lines of chemotherapy. Our findings further support the work of Pennington et al, 21 suggesting that a broader population of women with ovarian cancer may benefit from PARPi therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation